(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
This study was carried out at Darmini- Lattakia -syria, during 2016. Six genotypes from chickpeas (Provided by GASAR) were planted in randomized complete block design (R.C.B.D).The results showed that the genotypes (AL Hasakah, AL Pakistan, Daraa) were superior to all genotypes in germination earliness, however, the genotypes (Cyprus, AL Pakistan) were superior in delay flowering; and genotype ( AL Pakistan) was superior in delay harvesting, While the genotype (AL Hasakah) was superior in pods number, seeds number per plant and yield. Results showed that positive significant correlation between days for germination and days for flowering and harvest, and also there were positive significant correlation between yield and number of pods and seeds per plant, The results were supported by calculating the regression coefficient. نفّذت التجربة في قرية درميني التابعة لمحافظة اللاذقية عام 2016 , حيث زرع ستة طرز وراثية من الحمص المزروع ( تم الحصول عليها من مركز الهيئة العامة للبحوث العلمية الزراعية) بعلاً ووفق تصميم القطاعات العشوائية الكاملة. بينت النتائج تفوق الطرز ( الحسكة, باكستان, درعا) معنوياً بالتبكير بالإنبات بمتوسط (20, 20, 21) يوماً على التوالي, في حين تفوق الطرازان (قبرص, باكستان) معنوياً بالتبكير بالإزهار بمتوسط (74.5, 76.8) يوماً على التوالي, وتفوق الطراز (الباكستان) معنوياً بالتبكير بالنضج التام بمتوسط (140.3) يوماً, كما أبدى الطراز ( الحسكة ) تفوقاً معنوياً على باقي الطرز المدروسة بصفة عدد القرون بمتوسط (38.5) قرن, وصفة عدد البذور بالنبات بمتوسط (39.5) بذرة/ النبات وأيضاً بالغلة البذرية بمتوسط (3.6) غ/النبات, وأظهرت النتائج وجود علاقة ارتباط موجبة ومعنوية بين عدد الأيام للإزهار والنضج التام r = 0.88**)), كما وجدت علاقة ارتباط موجبة ومعنوية بين عدد القرون وعدد البذور/ النبات(*r = 0.99*) وبين كلٍ منهما مع الغلة البذرية غ/ النبات r = 0.89**)), وأُكدت صحة النتائج بحساب معامل الانحدار الخطي لصفة الغلة البذرية على كل من صفتي عدد القرون وعدد البذور في النبات (0.1 = β ).